2021
DOI: 10.1002/ejp.1822
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a pain educational video intervention upon child pain‐related outcomes: A randomized controlled study

Abstract: Background: Pain neuroscience education (PNE) has received increasing research attention demonstrating beneficial effects on pain-related outcomes in adults.Conversely, studies on the effectiveness of PNE in children are scarce. Methods: This study investigated the effect of a pain educational video intervention on child pain-related outcomes (i.e. experienced pain intensity, pain-related fear and catastrophic worry about pain, pain threshold and pain knowledge) in healthy children undergoing an experimental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…Children—Prior to (t 1 ) and immediately after (t 2 ) the needle procedure, children self-reported on anticipated (t 1 ) and experienced (t 2 ) state (i.e., situation-specific) catastrophic thoughts about the needle procedure using an adaptation of the PCS-C [ 37 ]. In line with previous research [ 46 , 47 , 48 , 49 , 50 ], we used a state version of the PCS-C, including 3 items, with 1 adapted item from each of the 3 subscales (rumination: “To what extent do/did you keep thinking about how much pain the needle procedure could cause?”; magnification: “To what extent do/did you expect that, because of the pain, something serious would happen during the needle procedure?”; helplessness: “To what extent do/did you think you will not be able to endure the needle procedure because of the pain?”). Participants rated their anticipated or experienced catastrophic worry, respectively, regarding the needle procedure on an 11-point numeric rating scale ranging from 0 (“not at all”) to 10 (“extremely”).…”
Section: Methodsmentioning
confidence: 99%
“…Children—Prior to (t 1 ) and immediately after (t 2 ) the needle procedure, children self-reported on anticipated (t 1 ) and experienced (t 2 ) state (i.e., situation-specific) catastrophic thoughts about the needle procedure using an adaptation of the PCS-C [ 37 ]. In line with previous research [ 46 , 47 , 48 , 49 , 50 ], we used a state version of the PCS-C, including 3 items, with 1 adapted item from each of the 3 subscales (rumination: “To what extent do/did you keep thinking about how much pain the needle procedure could cause?”; magnification: “To what extent do/did you expect that, because of the pain, something serious would happen during the needle procedure?”; helplessness: “To what extent do/did you think you will not be able to endure the needle procedure because of the pain?”). Participants rated their anticipated or experienced catastrophic worry, respectively, regarding the needle procedure on an 11-point numeric rating scale ranging from 0 (“not at all”) to 10 (“extremely”).…”
Section: Methodsmentioning
confidence: 99%
“…On the true preventative side, very recently, pain education is being delivered to and studied in a one-on-one format in healthy children [36,37] as well as in larger groups at middle schools [31,[38][39][40][41][42][43]. Rheel et al [36] found that healthy children (aged 8-15 years) who watched a 15minute pain education video before an experimental heat pain task had higher pain knowledge and higher heat pain thresholds after watching the video compared to a group of children who did not watch this video. However, no group differences were found on experienced pain intensity, painrelated fear and pain catastrophizing during the heat pain task.…”
Section: Pain Education As a Preventive Strategymentioning
confidence: 99%
“…22 According to a recent Cochrane report, there is no evidence to support or refute the use of opioids for treating cancer-related pain in children and adolescents, 21 highlighting the importance of nonpharmacological pain management strategies. One nonpharmacological treatment approach increasingly researched and implemented in pediatric and adolescent clinical 43,44 and nonclinical [45][46][47][48] populations is pain science education (PSE). PSE, also called pain neuroscience education, 49 explains pain, 50 therapeutic neuroscience education 51,52 or pain education, 53 is a conceptual change strategy facilitating patients' understanding of the biopsychosocial aspects of pain, including the contributing role of (neuro)physiological, psychosocial, and environmental factors.…”
Section: Pain Science Education As Part Of Comprehensive Pain Carementioning
confidence: 99%
“…PSE comprises one or more patient-tailored educational sessions, typically face-to-face between a therapist and patient, and supported by educational materials. Evidence in children and adolescents in clinical 43,44 and nonclinical [45][46][47][48] settings shows that PSE results in increased pain knowledge, 43,[45][46][47][48][55][56][57] more functional pain beliefs, 46,56,57 less catastrophic worry about pain, 58 less pain-related fear, 44 less functional disability, 44 less medication use, 45 higher pain thresholds, 44,48 higher school attendance, 45 and decreased fear of physical activity. 56 There is less evidence that PSE for both adults and children results in reduced pain intensity, 43,44,59 pressure pain thresholds, 60,61 or anxiety.…”
Section: Pain Science Education As Part Of Comprehensive Pain Carementioning
confidence: 99%